2021
DOI: 10.5585/iji.v9i1.18076
|View full text |Cite
|
Sign up to set email alerts
|

Resource orchestration in innovation ecosystems: a comparative study between innovation ecosystems at different stages of development

Abstract: Objective of the study: The present study aimed to answer the following question: How are resources orchestrated to generate innovation in innovation ecosystems?Methodology/Approach: An exploratory qualitative research was conducted through documentary analysis, non-participant observation, and in-depth interviews with actors from two Brazilian ecosystems in different stages of development: 4th District (emerging) and Porto Digital (growth).Originality/Relevance: Innovation ecosystems can be understood as a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 49 publications
(86 reference statements)
1
15
0
Order By: Relevance
“…Here, we extend the previous work by Heaton et al . (2019) and Bittencourt et al . (2021) on the role of a hub-firm in industrial ecosystems.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Here, we extend the previous work by Heaton et al . (2019) and Bittencourt et al . (2021) on the role of a hub-firm in industrial ecosystems.…”
Section: Discussionmentioning
confidence: 98%
“…(2021) on the role of a hub-firm in industrial ecosystems. While Bittencourt et al . (2021) found that the hub-firm was necessary to improve resource use when comparing two ecosystems, we go beyond that finding by considering how the hub-firm operationalises project creation and inception of collaborative project teams (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations